Boron SSZ-41, synthesis and use thereof

By introducing boron elements into the SSZ-41 molecular sieve and synthesizing boron zinc silicate molecular sieve with a specific structural guide agent, the problem of insufficient catalytic performance of the existing SSZ-41 molecular sieve is solved, and the efficient catalytic effect in the organic compound conversion reaction is achieved.

CN119789910APending Publication Date: 2025-04-08CHEVRON USA INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380062471.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing SSZ-41 molecular sieve failed to contain boron, limiting its catalytic properties in organic compound conversion reactions.

Method used

By using 1,1'-(1,4-butadiyl)bis[4-azazo-1-azonium bicyclic[2.2.2]octane] bications as structural guides, a boron-containing molecular sieve with SSZ-41 crystal structure, i.e. boron zinc silicate molecular sieve was successfully synthesized.

Benefits of technology

The novel molecular sieve exhibits unique catalytic capabilities in organic compound conversion reactions and has important value as an adsorption/separation material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119789910A_ABST
    Figure CN119789910A_ABST
Patent Text Reader

Abstract

A novel synthetic crystalline molecular sieve material referred to as boron SSZ-41 is provided. The boron SSZ-41 is a boron zinc silicate molecular sieve and has an SSZ-41 skeleton structure. The present invention relates to compounds that can be synthesized using a 1, 1 '-(1, 4-butanediyl) bis [4-aza-1-azonium bicyclo [2.2. 2] octane] dication as a structure directing agent. The boron zinc silicate SSZ-41 can be used in the conversion reaction and / or adsorption process of organic compounds.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Application Serial No. 63 / 402,820, filed on August 31, 2022, the entire disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to small crystal size SSZ-41 molecular sieves, their synthesis and their use as adsorbents and catalysts for organic conversion reactions. Background Art

[0004] Molecular sieves are a class of commercially important materials that have different crystal structures with defined pore structures as shown by different X-ray diffraction (XRD) patterns and have specific chemical compositions. The crystal structure defines cavities and pores that are characteristic for a particular type of molecular sieve.

[0005] Providing new molecular sieves with differences in crystal structure and composition can produce unique catalysts or adsorption / separation materials. Changing the crystal structure is always fraught with difficulty, but success can bring rewards in the form of new catalysts for organic compound conversion reactions. U.S. Patent No. 5,591,421 discloses the preparation of SSZ-41. However, it does not disclose boron SSZ-41. Summary of the invention

[0006] According to the present invention, a novel crystalline molecular sieve called boron SSZ-41 is synthesized using 1,1′-(1,4-butanediyl)bis[4-aza-1-azoniabicyclo[2.2.2]octane] dication as a structure directing agent (SDA). It has been found that the synthesis successfully provides a boron-containing molecular sieve having the SSZ-41 crystal structure, i.e., a borozinc silicate molecular sieve.

[0007] In a second aspect, a method for synthesizing a boron zinc silicate molecular sieve having an SSZ-41 framework structure is provided, the method comprising: (1) forming a reaction mixture comprising: (a) a silicon source such as a FAU framework type zeolite; (b) a zinc source; (c) a structure directing agent (Q) comprising a 1,1′-(1,4-butanediyl)bis[4-aza-1-azoniabicyclo[2.2.2]octane] dication; (d) a boron source; (e) a hydroxide ion source; (f) water; and (g) a seed crystal; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the boron molecular sieve.

[0008] In a third aspect, a method for converting a feedstock comprising an organic compound into a conversion product is provided, the method comprising the following steps: (i) contacting the feedstock with a catalyst under organic compound conversion conditions to produce an effluent containing the conversion product, the catalyst comprising a boron zinc silicate molecular sieve having an SSZ-41 framework structure; and (ii) recovering the conversion product from the effluent.

[0009] Among other factors, the method of the present invention allows the acquisition of borozinc silicate SSZ-41 molecular sieve. This novel molecular sieve prepared by the method of the present invention can provide a unique ability as a catalyst in organic compound conversion reactions. The molecular sieve also has important value as an adsorption / separation material. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The attached figure is a solid state MAS NMR of the product of Example 1. The figure shows that the boron exists in a tetrahedral configuration. DETAILED DESCRIPTION

[0011] definition

[0012] The term "framework type" has the meaning described in "Atlas of Zeolite Framework Types" by Ch. Baerlocher, LB McCusker and DH Olsen (Elsevier, 6th revised edition, 2007).

[0013] As used herein, the term "as-synthesized" refers to the form of the molecular sieve after its crystallization and before the removal of the structure directing agent.

[0014] As used herein, the term "anhydrous" means that the molecular sieve is substantially free of both physically adsorbed water and chemically adsorbed water.

[0015] As used herein, the numbering scheme for the Periodic Table Groups is as disclosed in Chem. Eng. News 1985, 63(5), 26-27.

[0016] Synthesis of Boron Molecular Sieve

[0017] The borozinc silicate molecular sieve having an SSZ-41 framework structure can be synthesized by the following steps: (1) forming a reaction mixture comprising: (a) a silicon source; (b) a zinc source; (c) a structure directing agent (Q) comprising a 1,1′-(1,4-butanediyl)bis[4-aza-1-azoniabicyclo[2.2.2]octane]dianion; (d) a boron source; (e) a hydroxide ion source; (f) water; and (g) a seed crystal; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the borozinc silicate molecular sieve.

[0018] In one embodiment, the silicon source may comprise a FAU framework-type zeolite.

[0019] The reaction mixture may have a composition expressed in molar ratios within the ranges described in Table 1:

[0020] Table 1

[0021] wherein Q comprises a 1,1′-(1,4-butanediyl)bis[4-aza-1-azoniabicyclo[2.2.2]octane] dianion.

[0022] The silicon source may include a FAU framework type zeolite. The FAU framework type zeolite may be zeolite Y. The FAU framework zeolite may be an ammonium type zeolite or a hydrogen type zeolite (e.g., NH4 + -type zeolite Y, H + -type zeolite Y). The FAU framework type zeolite may have a SiO2 / Al2O3 molar ratio of at least 300 (e.g., 300 to 500, 300 to 600). The FAU framework type zeolite may comprise two or more zeolites. Typically, the two or more zeolites are zeolite Y with different silica:alumina molar ratios. Examples of suitable aluminosilicate zeolites include Y zeolites CBV720, CBV760, and CBV780 (commercially available from Zeolyst International) and Y zeolites HSZ-HUA385 and HSZ-HUA390 (commercially available from Tosoh). The FAU framework type zeolite may be used as the sole or primary silicon source in the reaction mixture. A silicon source that does not contain aluminum may be quite useful. In one embodiment, the silicon source does not contain Al.

[0023] The FAU framework type zeolite can be a zinc exchanged zeolite (e.g., zinc exchanged zeolite Y), wherein the zeolite can also be a source of zinc metal for the reaction mixture. "Zinc exchanged zeolite" refers to an aluminosilicate zeolite in which the zinc metal is located on the surface and / or within the cages and / or pores of the aluminosilicate zeolite. It does not refer to an aluminosilicate in which the zinc metal is in the aluminosilicate framework.

[0024] Additionally or alternatively, the zinc source may be a zinc salt of an organic or inorganic acid. Representative zinc salts include zinc formate, zinc acetate, zinc citrate, zinc chloride, zinc bromide, zinc nitrate, and zinc sulfate.

[0025] If lithium is added, sources of lithium include lithium hydroxide and other lithium salts, particularly lithium halides such as lithium chloride.

[0026] Suitable boron sources may include boric acid, which is preferred.

[0027] The source of hydroxide ions may be lithium hydroxide. Structure directing agents may also be used to provide hydroxide ions.

[0028] The structure directing agent (Q) comprises a 1,1'-(1,4-butanediyl)bis-4-aza-1-azoniabicyclo[2.2.2]octane dication ("[DABCO-(CH2)4-DABCO] 2+ ”):

[0029]

[0030] Suitable sources of Q are hydroxides, chlorides, bromides and / or other salts of diquaternary ammonium compounds.

[0031] The reaction mixture also contains seed crystals, typically from a previously synthesized borozinc silicate SSZ-41, ideally in an amount of 0.1 to 20 wt % (e.g., 0.5 to 10 wt %) relative to the total weight of SiO2 in the reaction mixture. Seeding can be beneficial in improving the selectivity of the borozinc silicate SSZ-41 and / or shortening the crystallization process. Although boron SSZ-41 seed crystals are preferred, in one embodiment, seed crystals of SSZ-41 zeolite previously prepared in the absence of boron can be used.

[0032] It should be noted that the reaction mixture components can be supplied by more than one source. In addition, two or more reaction components can be provided by one source. The reaction mixture can be prepared batchwise or continuously.

[0033] Crystallization and post-synthesis processing

[0034] The desired crystallization of the molecular sieve from the above reaction mixture can be carried out under static, tumbling or stirring conditions in a suitable reaction vessel such as a polypropylene tank or a Teflon liner or a stainless steel autoclave at a temperature of 100° C. to 200° C. (e.g., 130° C. to 180° C.) for a time sufficient for crystallization to occur at the temperature used, such as about 1 day to 14 days (e.g., 3 days to 10 days). Crystallization is usually carried out in an autoclave under pressure so that the reaction mixture is subjected to autogenous pressure.

[0035] Once the desired molecular sieve crystals are formed, the solid product can be separated from the reaction mixture by conventional mechanical separation techniques such as centrifugation or filtration. The recovered crystals are washed with water and then dried for a few seconds to a few minutes (e.g., 5 seconds to 10 minutes for flash drying) or a few hours (e.g., 4 hours to 24 hours for oven drying at 75° C. to 150° C.) to obtain the molecular sieve crystals as they were after synthesis. The drying step can be carried out under vacuum or atmospheric pressure.

[0036] As a result of the crystallization process, the recovered crystalline molecular sieve product contains within its pores at least a portion of the structure directing agent used in the synthesis.

[0037] The as-synthesized molecular sieve may be subjected to heat treatment, ozone treatment or other treatment to remove part or all of the structure directing agent used in its synthesis. The removal of the structure directing agent may be carried out using a heat treatment (e.g., calcination), wherein the as-synthesized material is heated in an atmosphere selected from air, nitrogen, or a mixture thereof at a temperature sufficient to remove part or all of the structure directing agent. Although pressures below atmospheric pressure may be used for heat treatment, atmospheric pressure is desirable for reasons of convenience. The heat treatment may be carried out at a temperature of at least 370° C. (e.g., 400° C. to 700° C.) for at least 1 minute, and generally not longer than 20 hours (e.g., 1 to 8 hours).

[0038] As required, any extra-framework metal cations (such as Li + ) can be replaced by ion exchange with other cations according to techniques well known in the art. Replacement cations include metal ions, hydrogen ions, hydrogen precursors (such as ammonium ions) and mixtures thereof.

[0039] Characterization of Molecular Sieve

[0040] In its as-synthesized form and in anhydrous form, the borozinc silicate SSZ-41 molecular sieve may have a chemical composition expressed in molar ratios within the ranges described in Table 2:

[0041] Table 2

[0042] wherein Q comprises a 1,1′-(1,4-butanediyl)bis[4-aza-1-azoniabicyclo[2.2.2]octane] dianion.

[0043] Thus, the composition can be said to comprise a molar relationship of B2O3:(n)(SiO2), wherein in one embodiment n≥10, in another embodiment n≥15, and in one embodiment n is between about 15 and 20.

[0044] Molecular sieve boron SSZ-41 has a powder X-ray diffraction (XRD) pattern including at least the peaks listed in Table 3 below in the as-synthesized form of the molecular sieve and at least the peaks listed in Table 4 below in the calcined form of the molecular sieve.

[0045] Table 3

[0046] Characteristic XRD peaks of as-synthesized boron SSZ-41

[0047] Table 4

[0048] Characteristic XRD peaks of calcined boron SSZ-41

[0049] The X-ray diffraction data reported herein are collected by standard techniques using copper K-α radiation. The determination of parameter 2-θ is affected by both manual and mechanical errors, and the combination of the two can impose an uncertainty of about ± 0.10 ° on each reported 2-θ value. It should be understood that when the corresponding value of d-spacing is converted to using Bragg's law, the d-spacing value has a deviation determined based on the corresponding deviation ± 0.10 degree 2-θ. The relative intensity I / Io of the line represents the ratio of the intensity of the strongest line above the peak intensity and the background. The relative intensity is given with symbols VS=very strong (>60), S=strong (≥40 and ≤60), M=medium (≥20 and <40) and W=weak (<20).

[0050] Due to changes in the lattice constant, changes in the molar ratio of the framework material of the sample can cause slight changes in the diffraction pattern. In addition, disordered materials and / or sufficiently small crystals will affect the shape and intensity of the peaks, resulting in significant peak broadening. Changes in the organic compounds used in the preparation can also cause slight changes in the diffraction pattern. Calcination can also cause small shifts in the XRD pattern. Despite these minor perturbations, the basic lattice structure remains unchanged.

[0051] Industrial Applicability

[0052] Molecular sieve borozinc silicate SSZ-41 (in which part or all of the structure directing agent is removed) can be used as an adsorbent or catalyst to catalyze various organic compound conversion processes. Particularly suitable is the use of borozinc silicate SSZ-41 in reforming processes.

[0053] Catalytic reforming is one of the basic oil refining methods that light hydrocarbon feedstock (often referred to as naphtha feedstock) is upgraded. Products from catalytic reforming may include high-octane gasoline, aromatics (e.g., benzene, toluene, xylene, and ethylbenzene) and / or hydrogen that can be used as automobile fuel. The reactions usually involved in catalytic reforming include dehydrogenation cyclization, isomerization, and dehydrogenation of naphtha-based hydrocarbons, wherein the dehydrogenation cyclization and dehydrogenation of straight-chain and slightly branched alkanes and the dehydrogenation of cycloalkanes lead to the production of aromatics. Due to the low value of the resulting light hydrocarbon products, dealkylation and hydrocracking are usually undesirable.

[0054] The borosilicate SSZ-41 catalyst used in the reforming reaction typically includes a Group VIII metal such as platinum or palladium, or a Group VIII metal plus a second catalytic metal that acts as a promoter. Examples of metals that can be used as promoters include rhenium, tin, tungsten, germanium, cobalt, nickel, rhodium, ruthenium, iridium, or a combination thereof. One or more catalytic metals can be dispersed on a support such as alumina, silica, or silica-alumina.

[0055] As in the case of many catalysts, it may be desirable to combine the borozinc silicate SSZ-41 material of the present invention with another material that tolerates the temperature and other conditions used in the organic conversion process. Such materials include active and inactive materials and synthetic or naturally occurring zeolites and inorganic materials such as clays, silica and / or metal oxides such as alumina. The latter may be naturally occurring, or in the form of a gelatinous precipitate or gel, including a mixture of silica and metal oxides. The use of a material in combination with boron SSZ-41 (i.e., in combination with it or present during the synthesis of new crystals, the material is active) tends to change the conversion rate and / or selectivity of the catalyst in certain organic conversion processes. Inactive materials are suitable for use as diluents to control the amount of conversion in a given process so that the product can be obtained in an economical and orderly manner without the need to adopt other means of controlling the reaction rate. These materials can be introduced into naturally occurring clays (e.g., bentonite and kaolin) to improve the crush strength of the catalyst under commercial operating conditions. These materials (i.e., clays, oxides, etc.) act as binders for the catalyst. It is desirable to provide a catalyst with good crush strength because in commercial use it is desirable to prevent the catalyst from breaking down into a powdery material.These clay and / or oxide binders are usually used solely for the purpose of improving the crush strength of the catalyst.

[0056] Naturally occurring clays that can be composited with the SSZ-41 material include the montmorillonite and kaolin families, which include subbentonites, and kaolins commonly referred to as Dixie, McNamee, Georgia, and Florida clays, or other clays in which the major mineral components are halloysite, kaolinite, dickite, nacrite, or anthracite. Such clays can be used in their original state, such as as mined, or they can have been initially subjected to calcination, acid treatment, or chemical modification. Binders that can be used for composites with SSZ-41 also include inorganic oxides such as silica, zirconia, titania, magnesia, beryllia, alumina, and any combination thereof.

[0057] In addition to the above materials, borozinc silicate SSZ-41 can be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.

[0058] The relative proportions of the borozinc silicate SSZ-41 and the inorganic oxide matrix can vary widely, with the borozinc silicate SSZ-41 content being 1 to 90 wt % (eg, 2 to about 80 wt %) of the composite.

[0059] Boron zinc silicate SSZ-41 reforming catalyst can be adopted in the form of pill, ball, particle, fragment or various special shapes, placed in the reaction zone as fixed bed, and the charge can be in liquid phase, gas phase or mixed phase and in upward, downward or radial flow.Alternatively, the reforming catalyst can be used in a moving bed or fluidized-solid method, wherein the charge passes through a turbulent bed of subdivided catalyst upwards.However, due to less catalyst consumption and other operational advantages, a fixed bed system or a dense phase moving bed system is preferred.In a fixed bed system, (by any suitable heating member) the feed is preheated to the desired reaction temperature, and then sent into the reaction zone of the fixed bed containing the catalyst.The reaction zone can be one or more separate reactors, wherein there is a suitable member at the reactor inlet to keep the desired temperature.Because the reforming reaction is usually endothermic in nature, the temperature must be maintained.

[0060] The actual reforming conditions will generally depend, at least in part, on the feed used, whether highly aromatic, paraffinic or cycloalkyl, and the desired product octane number as well as the desired amount of hydrogen production.

[0061] Example

[0062] The following illustrative examples are intended to be non-limiting.

[0063] Example 1

[0064] The synthesis of borozinc silicate SSZ-41 is described. LiOH (anhydrous) = 0.05 g, zinc acetate dihydrate = 0.136 g, boric acid = 0.06 g, Tosoh Hua 390 (FAU zeolite) = 0.90 g, 3.33 g of 1.27 M SDA solution and 5.25 g of water were added to a Teflon cup of a Parr 23 mL reactor. Seeds of SSZ-41 zeolite previously prepared without boron (3% of total SiO2 solids) were added. The Si / B ratio in this synthesis was about 15. The reaction mixture was heated at 160°C and 43 RPM tumbling for 10 days. The product was a good borozinc silicate SSZ-41 material. The product was analyzed for boron = 0.16 wt% boron. Solid-state MASNMR (see attached figure) showed that boron was present in a tetrahedral configuration, which indicates lattice substitution.

[0065] Example 2 Calcination of borozinc silicate SSZ-41

[0066] The product of Example 1 was calcined to 540°C under nitrogen purge in a temperature program and then SDA was removed. The product retained the XRD pattern of SSZ-41.

[0067] Example 3 Boron exchange aluminum

[0068] Exchange experiments were performed, also demonstrating that the borosilicate product of Example 1 had boron in the framework. 0.4 grams of calcined borosilicate zinc silicate SSZ-41 (Example 2) was placed in a vial, and 20 grams of a 0.2 molar solution of aluminum nitrate nonahydrate was added to produce an excess of Al relative to B in the zeolite. The solution was heated at 95°C for 4 days without stirring. The product was recovered by filtration and washed first with 0.1 HCl solution (to remove any Al still in solution), and then with water. The product was dried, and XRD showed no change. Next, the now aluminum-substituted boron SSZ-41 was tested for acidity using n-propylamine as the adsorbate. The result was that strong acid sites (characteristic of Al in the zeolite lattice) were now observed, with measurements close to 100 micromolar ammonia measured at temperatures above 400°C.

[0069] Example 4 Platinum Addition

[0070] The calcined and ammonium exchanged zeolite of Example 2 (0.63 g) and 0.0126 g of platinum were added to 12.9 g of water, wherein the platinum was generated from tetraamine platinum chloride hydrate. Stirring was carried out at room temperature for 24 hours, and then the solid was filtered and calcined to 300° C. The solid was then pressed and divided into 24 / 40 pieces and loaded into the reactor.

[0071] Example 5 Pretreatment of Catalytic Naphtha Reforming Catalyst

[0072] The catalytic naphtha reforming catalyst prepared in Example 4 was sulfided. The sulfidation reaction was carried out in a downflow fixed bed reactor system. The procedure is described as follows:

[0073] The catalyst was divided into 24-40 pieces and then loaded into the center of a stainless steel tube reactor. The catalyst (0.53 g dry weight, measured by TGA (thermogravimetric analysis) at 1112°F) was first dried in a N2 stream (300 mL / min) at a heating rate of 10°F / min from room temperature to 400°F, and kept at 400°F for 30 minutes. To reduce the platinum in the catalyst, the catalyst was then heated from 400°F to 900°F in a H2 stream (300 mL / min) at a heating rate of 5°F / min, and kept at 900°F for 30 minutes. Finally, the catalyst was cooled to 800°F to start the sulfidation reaction.

[0074] The feed that is applied to the sulfidation reaction is anhydrous n-octane containing 200 ppm sulfur (in terms of dimethyl disulfide).Sulfidation was carried out for 60 minutes at 800°F and atmospheric pressure.H2 and liquid feed flow rate are 30 mL / min and 0.43 mL / min respectively.After sulfidation, the catalyst is heated to 900°F from 800°F in a few minutes in H2 stream (300 mL / min), and then heated in addition for 30 minutes at 900°F to remove the excessive sulfur substances that are blocked in the hole of the catalyst and / or on the surface.Finally, the catalyst is heated or cooled to a preset reaction temperature (e.g. 850°F or 950°F) in 2 hours in identical H2 stream (300 mL / min), to prepare the catalytic naphtha reforming test in the beginning embodiment 6.

[0075] Example 6 Catalytic Naphtha Reforming Experimental Procedure

[0076] Following the sulfiding procedure described in Example 5, the catalytic naphtha reforming reaction was carried out as described below.

[0077] As described in Example 5, the catalyst was heated or cooled to the preset reaction temperature (950°F for Example 8) in the same H2 flow (300 mL / min) within 2 hours to prepare for the start of the catalytic naphtha reforming test in this example. At the same time, the reactor system was pressurized to the preset pressure (150 psig for Example 8). At the same time, the H2 flow was adjusted to the preset rate (14 mL / min for Example 8). The feed rate was 1.55 mL / h (for Example 8).

[0078] In the following examples, catalytic naphtha reforming experiments were conducted using the naphtha feed described in Example 7 at a hydrocarbon WHSV of 2.2 and a hydrogen:hydrocarbon molar ratio of 3.0.

[0079] Example 7 Feed for Catalytic Naphtha Reforming Test

[0080] Table 5 shows the GC analysis data of the feed used in the catalytic naphtha reforming test of the present invention, and the GC results of the catalytic naphtha reforming test product of Example 8 relative to the catalyst described in Example 5. The GC data were obtained via online analysis.

[0081] Example 8 Products from Catalytic Naphtha Reforming Tests

[0082] The GC analysis data for the feed of Example 7 used in the catalytic naphtha reforming test is given in Table 5, along with the results of the catalytic naphtha reforming test product of this Example relative to the catalyst described in Example 5. The catalytic naphtha reforming test was conducted at 950°F, 150 psig, with a hydrocarbon WHSV of 2.2 and a hydrogen:hydrocarbon molar ratio of 3.0.

[0083] Table 5

[0084] The products in Table 5 show an increase in aromatics and gasoline octane. Boron-SSZ-41 successfully reformed the feedstock of Example 7.

[0085] As used herein, the words "comprising" are intended to be an open transition, meaning the inclusion of the recited elements but not necessarily the exclusion of other unrecited elements. The phrase "consisting essentially of is intended to mean the exclusion of other elements of any critical importance to the composition. The phrase "consisting of is intended to be a transition, meaning the exclusion of all elements other than the recited elements, except for only trace amounts of impurities.

[0086] To the extent not inconsistent with this document, all patents and publications referenced herein are hereby incorporated by reference. It will be understood that some of the above-mentioned structures, functions, and operations of the above-mentioned embodiments are not necessary for practicing the present invention, and are included in the specification only for the completeness of one or more exemplary embodiments. In addition, it will be understood that the specific structures, functions, and operations set forth in the above-mentioned referenced patents and publications can be practiced in conjunction with the present invention, but they are not essential for the practice of the present invention. Therefore, it should be understood that the present invention can be practiced in different ways from the specific description without actually departing from the spirit and scope of the present invention as defined by the appended claims.

Claims

1. Molecular sieves, which have the following peaks in the as-synthesized form: And has boron in the framework.

2. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: B2O3:(n)(SiO2) Where n≥10.

3. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: B2O3:(n)(SiO2) Where n≥15.

4. The molecular sieve of claim 2, wherein n is about 15 to 20.

5. The molecular sieve according to claim 1, having a chemical composition comprising the following molar relationship: wherein Q comprises a 1,1′-(1,4-butanediyl)bis[4-aza-1-azoniabicyclo[2.2.2]octane] dianion.

6. The molecular sieve of claim 5, wherein the molecular sieve has a chemical composition comprising the following molar relationship: wherein Q comprises a 1,1′-(1,4-butanediyl)bis[4-aza-1-azoniabicyclo[2.2.2]octane] dianion.

7. The molecular sieve according to claim 1, which has at least the following peaks in the calcined form: And has boron in the framework.

8. A method for synthesizing a boron molecular sieve having a SSZ-41 framework structure, the method comprising: (1) forming a reaction mixture comprising: (a) silicon source; (b) a zinc source; (c) a structure directing agent (Q) comprising a 1,1′-(1,4-butanediyl)bis[4-aza-1-azoniabicyclo[2.2.2]octane]dianion; (d) a boron source; (e) a hydroxide ion source; (f) water; and (g) seed crystals; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the boron molecular sieve.

9. The method of claim 8, wherein the silicon source does not contain aluminum.

10. The method of claim 8, wherein the silicon source comprises a FAU framework type zeolite.

11. The method of claim 8, wherein the reaction mixture has the following composition expressed in molar ratio: 。 12. The method of claim 8, wherein the reaction mixture has the following composition expressed in molar ratio: 。 13. The method of claim 10, wherein the FAU framework-type zeolite is zeolite Y.

14. The method of claim 8, wherein the zinc source comprises a zinc salt of an organic or inorganic acid, a zinc-exchanged FAU framework type zeolite, or any combination thereof.

15. The method of claim 8, wherein the seed crystals comprise a molecular sieve having a SSZ-41 framework structure.

16. The method of claim 8, wherein the reaction mixture comprises 0.1 to 20 wt. % of seed crystals, relative to the total weight of SiO2 in the reaction mixture.

17. The method of claim 8, wherein the crystallization conditions are heating the reaction mixture at a temperature of 100°C to 200°C under autogenous pressure for a period of 1 day to 14 days.

18. A method for converting a feedstock comprising an organic compound into a conversion product, the method comprising the steps of: (i) contacting the feedstock with a catalyst under organic compound conversion conditions to produce an effluent containing conversion products, the catalyst comprising a borozinc silicate molecular sieve having an SSZ-41 framework structure; and (ii) recovering the conversion product from the effluent.

19. A molecular sieve prepared by the method of claim 9.

20. A molecular sieve prepared by the method of claim 12.

Citation Information

Patent Citations

  • Zeolite SSZ-41

    US5591421A